The Digital Paradigm in Contemporary Architecture - Mediati, Domenico (img journal, 2023)
The architecture of the 20th century has been largely affected by changes in the field of technology. In particular, the evolution of digital representation has led to new visions of contemporary architectural space. Expressive freedoms, which in the pre-digital era stemmed from visionary approaches, now become feasible thanks to modern modelling technologies. They determine a mutation of working processes and creative elaboration, proving to be more than just a mechanical tool without theoretical-speculative implications. Transformation of reality into updatable and modifiable data flows leads towards a new weltanschauung, characterised by the modern paradigms of precariousness and flexibility. Digital world, based on processing of algorithms and information, becomes a link between art and mathematics. The theoretical universe based on the fourth dimension and non-Euclidean geometries, which had produced interesting artistic effects in the avant-garde movements of the 20th century, now finds a means of expression in the field of architecture. The paper explores implications that digital technologies have had on mutations of contemporary architecture: from the fluid and deconstructed shapes linked to multidimensional experiments to the most recent experiences, placed at the border between art and architecture, that are experimenting with the transfer of digital language into the real world.